SEROPREVALENCE OF COELIAC DISEASE IN SHORT STATURED CHILDREN IN SOUTH INDIA: A HOSPITAL-BASED STUDY - VASANTH PERUMAL; UMA GAYATHRI BAGAVATHI PERUMAL; SYED MOHAMMED HASSAN ALI; MANJUNATH VADDAMBAL (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: The objective of this study was to assess the seroprevalence of coeliac disease among children with short stature in a tertiary care setting in South India. Methods: A prospective observational study was conducted at JSS Hospital, Mysuru, from November 2018 to August 2020. Children aged 2–18 years with height <−2 standard deviation for age and sex were enrolled after informed consent. Detailed clinical evaluation, anthropometric measurements, and mid-parental height were recorded. Serum tissue transglutaminase immunoglobulin A (tTG-IgA) levels were estimated using enzyme-linked immunosorbent assay. Children with positive results (>20 U/mL) were referred for further gastroenterological evaluation. Additional tests such as hemoglobin, thyroid stimulating hormone, and bone age X-rays were done as clinically indicated. Results: Out of 5450 children screened, 107 with short stature were included in the study. Of these, 92 (86%) had short stature and 15 (14%) had severe short stature. The most common etiology was familial short stature (43.9%), followed by idiopathic (19.6%), nutritional (15.9%), and constitutional delay in growth and puberty (11.2%). Only one child (0.9%) tested seropositive for coeliac disease. A weak but statistically significant correlation was observed between height and tTG-IgA levels (p=0.022). Conclusion: The seroprevalence of coeliac disease in children with short stature in South India was found to be low (0.9%) compared to Northern Indian data. However, given the treatable nature of coeliac disease, screening remains crucial in the evaluation of short stature. Larger, multicentric studies with confirmatory biopsy and IgA deficiency assessment are warranted to better delineate the true prevalence in Southern India.